Predicting Investment Feasibility in Perumda Establishment Using Payback Period, Net Present Value, and Internal Rate Return - Citra Sarasmitha; Karina Setia Utami (Jurnal Multidisiplin Madani, 2023)
This study examines the feasibility of investing in the establishment of a Regional Public Company in the field of rice distributors in the Yahukimo Regency, Papua. The investment feasibility analysis used consists of evaluating the payback period, Net Present Value, and Internal Rate Return. The analysis is also combined with various possible conditions, namely pessimistic, moderate and optimistic conditions. The type of data used is secondary data with a qualitative descriptive research approach. The results of the study show that the attitude of PERUMDA of Yahukimo district in the field of rice distribution is that the Payback Period, NPV, and IRR values show that they are feasible. The feasibility of investing in PERUMDA as a rice distributor is feasible in optimistic, moderate and pessimistic conditions. The establishment of the New PERUMDA will contribute to the absorption of rice production by the Yahukimo Regency community as a business process on the upstream side. Meanwhile, the business processes on the downstream side will have an impact on increasing PAD from the company's operating profit from the sale of rice